Errata: Formulação nodal aplicada a um problema de transporte bidimensional em geometria cartesiana [Scientia Plena 11, 081315 (2015)] - Ferreira, Carlos E. S.; Emmendorfer, Leonardo R.; Prolo Filho, João F. (Scientia Plena, 2015)
Errata.